A Compendium Review of the Global Epidemiology of Ticks and Tick-borne Diseases: Regional Insights from Türkiye - İnci, Abdullah; Özdarendeli, Aykut; Yıldırım, Alparslan; Sohel, Mahmodul Hasan; Özübek, Sezayi; Orkun, Ömer; Aktaş, Münir (My University, 2026)
Vector-borne diseases have historically posed significant threats to plants, humans, domestic animals, and wildlife, with their impact being especially pronounced in tropical and subtropical regions. Among these, tick-borne diseases (TBDs) have emerged as an increasingly critical global concern. This growing threat is largely driven by the expanding geographic range of ticks and the wide array of pathogens they transmit, including viruses, bacteria, protozoa, nematodes, fungi, and infectious prion proteins. The global cumulative economic impact of the challenges caused by ticks and TBDs contributes and exacerbates the persistence of poverty and food insecurity, particularly in resource-limited and low-income regions. This multifactorial burden is further compounded by a complex network of anthropogenic factors, including climate change, habitat fragmentation and ecological degradation, rapid urbanization, changes in agroecosystem management, the resurgence of wildlife reservoirs, and increased anthropozoonotic mobility. Additionally, long-distance and intercontinental migratory birds serve as important ecological carrier hosts, naturally facilitating the widespread distribution and geographic expansion of ixodid tick populations and their associated pathogen complexes. Exacerbating these challenges are regional conflicts, weak environmental and social governance, and rising antimicrobial resistance, which complicate prevention and control efforts of TBDs. Due to the effects of numerous anthropogenic factors-primarily global warming-the risk potential of emerging and re-emerging TBDs is increasing day by day, along with the zoogeographic distribution of ticks and the global challenges they pose. From a global epidemiological perspective, the rising incidence and prevalence of TBDs hold significant implications for both medical and veterinary disciplines. This critical status necessitates an enhanced and comprehensive understanding of ticks, particularly with regard to pivotal aspects such as their vectorial capacity and pathogen transmission dynamics. According to ixodological records, approximately a total of 1,025 tick species, including fossil species, have been reported worldwide to date. Several of these species have also been documented in Türkiye. The current tick fauna reported from seven geographical regions of Türkiye comprises a total of 58 species: 8 species from 6 genera in the family Argasidae (Argas - 2 species, Carios - 1 species, Ornithodoros - 2 species, Alectorobius - 1 species, Alveonasus - 1 species and Otobius - 1 species) and 50 species from 7 genera in the family Ixodidae (Ixodes - 17 species, Rhipicephalus - 8 species, Dermacentor - 4 species, Hyalomma - 9 species, Haemaphysalis - 8 species, Alloceraea - 1 species and Amblyomma - 3 species). Notably, the genera Hyalomma and Ixodes have been reported as the most frequently associated with human infestations in Türkiye, highlighting their epidemiological significance and potential role in the transmission of tick-borne pathogens (TBPs). Many TBDs with zoonotic characteristics have been reported globally. These include approximately 100 viral diseases-about half of which are zoonotic-as well as numerous bacterial, protozoan, filarial nematode, fungal, and prion-related pathogens, the majority of which also exhibit zoonotic potential. In recent years, molecular epidemiological studies highlight the increasing importance of emerging TBDs. In particularly, closely monitoring TBPs in wildlife-such as transmissible prion proteins in deer and rickettsial pathogens identified in mountain goats and mountain sheep-and elucidating their zoonotic potential is critically important. In addition, the ecological importance of bat-associated tick species-especially those infesting cave-dwelling bats, such as Ixodes vespertilionis, Ixodes simplex, Ixodes ariadnae, Ixodes kaiseri, and Haemaphysalis erinacei-and their role as potential vectors for emerging and reemerging TBPs should not be overlooked. Major TBDs associated with substantial global economic losses-such as Lyme borreliosis, anaplasmosis, ehrlichiosis, babesiosis, and theileriosis-also present significant epidemiological and economic challenges in Türkiye. Notably, in the Turkish context, key TBDs including babesiosis, theileriosis, anaplasmosis, and ehrlichiosis have been documented in animals across all geographical regions, leading to considerable economic impact. Crimean-Congo hemorrhagic fever in humans has been observed predominantly in Central Anatolia and the inland areas far from the Black Sea coast, with rare cases occurring in other parts of the country. Lyme borreliosis has been reported most frequently in the Marmara Region, followed by Central Anatolia and the Mediterranean Region. The global threat of TBDs directly undermines key Sustainable Development Goals, prompting international initiatives such as the World Health Organization's "small bite, big threat" campaign and the One Health approaches and the actions, which aim to reduce zoonotic disease risks through cross-sectoral collaboration. The goal is to combat emerging and re-emerging TBDs through integrated strategies that encompass human, animal, and environmental health. Innovative strategies-including tick-derived microRNAs, CRISPR/Cas9 gene-editing, transfection systems, extracellular vesicle research, and DNA-and miRNA-based vaccines-show promise for disrupting tick biology and pathogen transmission. These advances, combined with integrated tick control programs, early warning systems, global monitoring, and open data sharing, are essential for effective tick and TBD management. Addressing this complex challenge requires international cooperation, interdisciplinary research, and an "ecocentric education" approach that fosters environmental stewardship and scientific literacy. Ultimately, halting tick spread and reducing the global burden of TBDs depends on sustained commitment to One Health principles, robust governance, and investment in research, education, and capacity-building. This compendium provides an overview of ticks, their distribution, vector competence, medical and veterinary importance, tick-pathogen-host interactions, emerging TBD threats, integrated control strategies, and the economic impacts of ticks and TBDs. ©Copyright 2026 Turkish Society for Parasitology - Available online at www.turkiyeparazitolderg.org.; Vektör kaynaklı hastalıklar, tarihsel olarak bitkiler, insanlar, evcil hayvanlar ve yaban hayatı için önemli tehditler oluşturmuş ve etkileri özellikle tropikal ve subtropikal bölgelerde belirginleşmiştir. Bunlar arasında kene kaynaklı hastalıklar (KKH’lar), giderek daha kritik bir küresel endişe kaynağı haline gelmiştir. Bu büyüyen tehdit, büyük ölçüde kenelerin genişleyen coğrafi yayılımı ve virüsler, bakteriler, protozoalar, nematodlar, mantarlar ve enfeksiyöz prion proteinleri dahil olmak üzere bulaştırdıkları çok çeşitli patojenlerden kaynaklanmaktadır. Keneler ve KKH’ların neden olduğu zorlukların küresel kümülatif ekonomik etkisi, özellikle kaynakları kısıtlı ve düşük gelirli bölgelerde yoksulluk ve gıda güvensizliğinin devam etmesine katkıda bulunmakta ve durumu daha da kötüleştirmektedir. Bu çok faktörlü yük, iklim değişikliği, habitat bozulması ve ekolojik bozulma, hızlı kentleşme, tarımsal ekosistem yönetimindeki değişiklikler, yaban hayatı rezervuarlarının yeniden canlanması ve artan antropozoonotik hareketlilik gibi karmaşık bir antropojenik faktör ağı tarafından daha da ağırlaştırılmaktadır. Ek olarak, uzun mesafeli ve kıtalararası hareket eden göçmen kuşlar, önemli ekolojik taşıyıcı konaklar olarak hizmet vererek, doğal olarak ixodid kene popülasyonlarının ve ilişkili patojen komplekslerinin yaygın dağılımını ve coğrafi yayılımını kolaylaştırmaktadırlar. Bu zorlukları daha da kötüleştiren bölgesel çatışmalar, zayıf çevresel ve sosyal yönetişim ve artan antimikrobiyal direnç, KKH’ların önlenmesi ve kontrol çabalarını zorlaştırmaktadır. Başta küresel ısınma olmak üzere çok sayıda antropojenik faktörün etkileri nedeniyle, ortaya çıkan ve yeniden ortaya çıkan KKH’ların risk potansiyeli, kenelerin zoocoğrafik dağılımı ve oluşturdukları küresel zorluklarla birlikte her geçen gün artmaktadır. Küresel epidemiyolojik bir bakış açısından, KKH’ların artan insidansı ve yaygınlığı hem medikal hem de veteriner hekimliği disiplinleri için önemli sonuçlar doğurmaktadır. Bu kritik durum, özellikle vektör kapasiteleri ve patojen bulaşma dinamikleri gibi temel hususlar açısından keneler hakkında gelişmiş ve kapsamlı bir anlayışı gerektirmektedir. İksodolojik kayıtlara göre, bugüne kadar dünya çapında fosil türler de dahil olmak üzere toplam 1,025 kene türü bildirilmiştir. Bu türlerden bazıları Türkiye’den de bildirilmiştir. Türkiye’nin yedi coğrafi bölgesinden bildirilen mevcut kene faunası toplam 58 türden oluşmaktadır: Argasidae familyasından 6 cinse ait 8 tür (Argas - 2 tür, Carios - 1 tür, Ornithodoros - 2 tür, Alectorobius - 1 tür, Alveonasus - 1 tür ve Otobius - 1 tür) ve Ixodidae familyasından 7 cinse ait 50 tür (Ixodes - 17 tür, Rhipicephalus - 8 tür, Dermacentor - 4 tür, Hyalomma - 9 tür, Haemaphysalis - 8 tür, Alloceraea - 1 tür ve Amblyomma - 3 tür). Özellikle Hyalomma ve Ixodes cinslerinin Türkiye’de insan enfestasyonlarıyla en sık ilişkilendirilen cinsler olarak bildirilmesi, epidemiyolojik önemlerini ve kene kaynaklı patojenlerin (KKP’ler) bulaşmasındaki potansiyel rollerini vurgulamaktadır. Dünya genelinde zoonotik özelliklere sahip birçok KKH bildirilmiştir. Bunlar arasında yaklaşık 100 viral hastalık (bunların yaklaşık yarısı zoonotiktir) ve çoğunluğu zoonotik potansiyel gösteren çok sayıda bakteriyel, protozoan, filarial nematod, fungal ve prionla ilişkili patojen bulunmaktadır. Son yıllarda moleküler epidemiyolojik çalışmalar, ortaya çıkan KKH’ların artan önemini vurgulamaktadır. Özellikle yaban hayatındaki KKP’lerin (geyiklerdeki bulaşıcı prion proteinleri ve dağ keçileri ile dağ koyunlarında tanımlanan riketsiyal patojenler gibi) yakından izlenmesi ve zoonotik potansiyellerinin açıklığa kavuşturulması kritik öneme sahiptir. Ayrıca, yarasalarla ilişkili kene türlerinin (özellikle mağaralarda yaşayan yarasaları enfeste eden Ixodes vespertilionis, Ixodes simplex, Ixodes ariadnae, Ixodes kaiseri ve Haemaphysalis erinacei gibi) ekolojik önemi ve ortaya çıkan ve yeniden ortaya çıkan KKP’ler için potansiyel vektörler olarak rolleri göz ardı edilmemelidir. Lyme borreliosis, anaplazmosis, ehrlichiosis, babesiosis ve theileriosis gibi küresel ekonomik kayıplara yol açan başlıca KKH’lar, Türkiye’de de önemli epidemiyolojik ve ekonomik zorluklara sebep olmaktadırlar. Özellikle Türkiye bağlamında, babesiosis, theileriosis, anaplazmosis ve ehrlichiosis gibi KKH’lar tüm coğrafi bölgelerden rapor edilmiş olup, büyük ekonomik kayıplara yol açmışlardır. İnsanlarda Kırım-Kongo hemorajik ateşi ağırlıklı olarak Orta Anadolu ve Karadeniz’in sahilden uzak iç kesimlerinde görülmüş olup, ülkenin diğer bölgelerinde de nadir olgular meydana gelmiştir. Lyme borreliosis en sık Marmara Bölgesi’nde bildirilmiş olup, bunu Orta Anadolu ve Akdeniz Bölgeleri takip etmiştir. KKH’ların küresel tehdidi, sürdürülebilir kalkınma hedeflerini doğrudan baltalamakta ve Dünya Sağlık Örgütü’nün “küçük ısırık, büyük tehdit” kampanyası ve sektörler arası iş birliği yoluyla zoonotik hastalık risklerini azaltmayı amaçlayan Tek Sağlık yaklaşımları ve eylemleri gibi uluslararası girişimleri teşvik etmektedir. Amaç, insan, hayvan ve çevre sağlığını kapsayan entegre stratejiler aracılığıyla ortaya çıkan ve yeniden ortaya çıkan KKH’larla mücadele etmektir. Kene kaynaklı mikroRNA’lar, CRISPR/Cas9 gen düzenleme, transfeksiyon sistemleri, hücre dışı vezikül araştırmaları ve DNA ve miRNA tabanlı aşılar gibi yenilikçi stratejiler, kene biyolojisini ve patojen bulaşmasını engellemede umut vadetmektedir. Entegre kene kontrol (EKK) programları, erken uyarı sistemleri, küresel izleme ve açık veri paylaşımı ile birleştirilen bu gelişmeler, etkili kene ve KKH yönetimi için hayati önem taşımaktadır. Bu karmaşık zorluğun üstesinden gelmek, uluslararası iş birliği, disiplinlerarası araştırma ve çevre yönetimini ve bilimsel okuryazarlığı destekleyen “ekosentrik eğitim” yaklaşımını gerektirir. Nihayetinde, kenelerin yayılmasını durdurmak ve KKH’ların küresel yükünü azaltmak; Tek Sağlık ilkelerini uygulamağa, güçlü yönetişim sergilemeğe ve araştırma, eğitim ve kapasite geliştirmeye ayrılan yatırıma bağlıdır. Bu derleme, keneler ve onların dağılımları, vektör yeterlilikleri, tıbbi ve veteriner önemleri, kene-patojen-konak etkileşimleri, ortaya çıkan KKH tehditleri, EKK stratejileri ve keneler ile KKH’ların kümülatif ekonomik etkileri hakkında genel bir bakış sunmaktadır.
Keywords: economic burden; Epidemiology; tick control; tick-borne diseases; ticks; Türkiye